DNA cleavage studies of some complexes of schiff base pyrimidine one derivatives - Obeid, Abeer Omar; Al-Aghbari, Sama; El-Shekeil, Ali; Al-Shuja'a, Omar M. (International Journal of Pharmaceutical Sciences and Research, 2021)
A series of metal complexes, namely, Ni (II), Zn (II), Cu (II) and Pt (II), have been synthesized with newly prepared biologically active ligands. These ligands and their functional groups were carefully designed and selected to display DNA cleavage effect. Schiff base compoundof 2 - methyl - 3 - aminobenzopyrimidine - 4 - one (L1) was prepared by condensation of an equimolar mixture of 2-methyl-3-aminobenzopyrimidine-4-one (0.01 mole) and 2-hydroxybenzaldehyde (0.01 mole) in ethanol (25 ml). Schiff base (L2) compound was prepared by condensation of a mixture of Schiff base (1) (0.02 mole) and o-phenylenediamine (0.01 mole) in ethanol (25 ml) and a catalytic amount of KOH. The mixture was refluxed for 36 hrs. Ligand L2 (1 mmole) was dissolved in hot methanol. The metal chloride (1 mmole) was then added and the mixture was stirred under reflux for 24 h. The structures of ligands and their complexes have been confirmed by spectroscopic data i.e. IR, 1HNMR, MS, electronic and elemental (CHN) analysis. All Compounds were screened for DNA cleavage and showed complete cleavage of CT-DNA.